Sistem Informasi E-Disposisi Perguruan Tinggi XYZ Dengan Metode FAST - Riki Afriansyah; M Setya Pratama (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
Good management in managing correspondence is very necessary for government agencies. In today's digital era, the management of mail administration using an correspondence service system is more effective and efficient than management using conventional methods. Bangka Belitung State Manufacturing Polman still uses conventional methods in managing mail administration. therefore an e-disposition information system is needed to make it easier to manage mail such as disposition and search for documents that are more efficient in terms of time. The information system can be accessed anywhere, making it easier for campus leaders and officials to make dispositions quickly. In designing this e-disposition information system using the FAST method. At the needs analysis stage using the UML method because the system developed is object-oriented and at the testing stage using the black box testing method. The results of this study that the functional e-disposition system runs well and a comparison of time measurements is obtained that to search and disposition takes less than 1 minute.